CFD modelling of the off-gas system HIsarna iron making process part 2: reflux chamber geometry modification and effects on flow behaviour. (14th September 2022) - Hosseini, Ashkan; Dhiman, Vinod; Meijer, Koen; Zeilstra, Christiaan; Hage, Johannes; Peeters, Tim; Offerman, Erik; Yang, Yongxiang
ABSTRACT: A three-dimensional computational fluid dynamics (CFD) model for the HIsarna off-gas system is set up and validated by real plant data. In the model detailed reaction mechanism and kinetic data for post-combustion of CO-H2 mixture and carbon particles are incorporated. The results are presented and discussed in another study (Part 1) by the same authors. In the present paper, the focus will be on geometry modification of the off-gas system and the effects on the operating parameters. The effect of this modification on heat loss, temperature profile, carbon conversion and gaseous phase composition across the off-gas system is investigated. It is shown that the modified geometry leads to a higher heat loss through the reflux chamber walls which can change the temperature profile and consequently species composition. The modified geometry also offers possibility of higher CO-H2 mixture and carbon particles conversion rate and reduce unwanted emission from the reflux chamber.